Scaffold mediated delivery of drugs/genes for promoting nerve regeneration via gene silencing/pathway inhibition after traumatic nerve injuries - Zhang, Na (Nanyang Technological University, 2021)
Axons damaged by traumatic injuries are unable to spontaneously regenerate in the adult central nervous system (CNS). Although the peripheral nervous system (PNS) has some regenerative capabilities, the ability of growth is often limited due to scar tissue formation that hinders axonal regeneration. Various biomolecules (i.e. genes/drugs) offer strategies for improving regeneration by enhancing the intrinsic growth capability of neurons and overcoming the inhibitory environment that prevents neurite outgrowth. Unfortunately, several bottlenecks remain and has been preventing the successful utilization of drugs/genes. First and foremost, is the lack of robust delivery platforms to deliver drugs/genes effectively in vitro and in vivo. Secondly and equally important, is the fact that despite the plethora of in vitro drug screening platforms available, such as micropillars and microfluidic devices, it remains difficult to translate in vitro outcomes to in vivo applications with good correlations. Consequently, the development of effective therapeutics, particularly targeting tissue regeneration, remains slow.